Pendamping Pembuatan Blogger Sebagai Media Pembelajaran di Era Digitalisasi Bagi Guru SMP Negeri 3 Satu Atap Kecamatan Secanggang - Nurmisdaramayani Nurmisdaramayani; Satria Wiguna (Institut Teknologi dan Bisnis Semarang, 2024)
Many students at SMP Negeri 3 Satu Roof, Secanggang District, seem to be just playing around in learning Islamic religious education. There are even some students who don't like learning the History of Islamic Culture because the learning process is carried out in a monotonous manner. The presence of bloggers as a learning medium is one of the important media in the growth of information dissemination in the world, most people in the world can now use the internet for the information they want with Blogger making it easier for interactions between students as a medium for certain subject matter. The method for implementing community service at SMP Negeri 3 Satu Roof Secanggang is through the planning stages, implementation stages and evaluation stages. The results of implementing PkM are an effort to help teachers at SMP Negeri 3 Satu Roof, Secanggang District, understand, use and integrate digital technology into the learning process in the form of improving teacher technology skills, increasing learning creativity, forming a blogger-based learning community, increasing involvement students, increasing student academic achievement and improving school image.